Immediate reconstruction with implant post-mastectomy with prepectoral versus submuscular technique: experience of a public oncological treatment center - Costa, Pedro Lima; Rosa, Yara Carolina Monte de Sena; Cordeiro, Gláucia Mesquita; Oliveira, Ana Gabriela Caldas; Viegas, Raquel Aranha; Guará, José Pereira (Mastology, 2024)
Introduction: Reconstruction techniques after mammary adenectomy with implant placement in the prepectoral space without the use of cell dermal matrix have been attracting more interest recently. However, data on the risk of complications, especially in patients treated in Brazil by the Brazilian Unified Health System, are scarce. Methods: This is a retrospective cohort study on women who underwent mammary adenectomy and immediate reconstruction with implants in a public hospital in Brazil, with survival analysis for implant extrusion and its associated factors. Results: Prepectoral and submuscular implant-based reconstruction had similar clinical outcomes. High axillary involvement (four or more lymph nodes) was the only factor associated with implant extrusion, regardless of the implant reconstruction techniques used. Conclusions: Tumor burden might interfere with the immediate implant-based breast reconstruction.